PELATIHAN PEMBELAJARAN DARING BERBASIS APLIKASI GOOGLE DI MASA PANDEMIK COVID-19 DI SMAN 8 KOTA BENGKULU - Hery Haryanto; Apriza Hongko Putra; Heriansyah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract The Covid-19 pandemic has become a global health emergency, many countries are implementing social and physical distancing and hygienic interventions to cut the transmission of the corona virus. The application of social and physical distancing is not yet known when it will end. So that social and physical distancing directly impacts the learning process. This global pandemic is changing from face-to-face learning to online learning. So that online learning is a necessity for teachers. However, in fact most of the teachers in secondary schools have not mastered this distance learning. The purpose of this PPM is to train teachers to use Google-based applications for the creation, management of materials, and evaluation of distance learning and to prepare teachers for the era of educational revolution 4.0. The training is carried out face-to-face and independent activities. The training materials include the use of Google Drive for storage of material files, the use of Google Classroom for distance learning, and the use of Google Forms for evaluating student learning. The total time required for this training is 35 hours. Twenty four of the 30 participants who can finish to the end. 60% of participants said it was very useful, 40 percent was useful. One hundred participants stated that materials related to the management and creation of material content, and evaluation with google-based applications were very helpful for online learning. The obstacles faced by the participants were: short time, internet quota, signals that were not always smooth, not being able to face to face, character learning was not visible. The ability of teachers to use information technology during the Covid-19 pandemic or normal conditions is a necessity for teachers in the era of the educational revolution 4.0. Abstrak Pandemik Covid-19 telah menjadi kedaruratan kesehatan global, banyak negara menerapkan social and physical distancing dan intervensi higinis untuk memutus penularan virus korona. Penerapan social and physical distancing belum diketahui kapan berakhirnya. Sehingga social and physical distancing secara langsung berdampak pada proses pembelajaran. Pandemik global ini merubah dari cara pembelajaran langsung tatap muka dengan pembelajaran daring. Sehingga pembelajaran daring merupakan suatu keniscayaan bagi para guru. Namun kenyataanya sebagian besar guru di sekolah menengah belum menguasai pembelajaran jarak jauh ini.Tujuan PPM ini adalah melatih para guru untuk menggunakan aplikasi berbasis Google untuk pembuatan, pengelolaan materi, dan evaluasi pembelajaran jarak jauh dan mempersiapakan para guru untuk menuju era revolusi pendidikan 4.0. Pelatihan dilakukan secara tatap muka langsung dan kegiatan mandiri. Materi pelatihannya adalah penggunaan Google Drive untuk penyimpanan berkas materi, penggunaan Google Classroom untuk pembelajaran jarak jauh, dan penggunaan Google Form untuk evalusi pembelajaran siswa. Total waktu yang dibutuhkan untuk pelatihan ini selama 35 jam. Dua puluh empat dari 30 peserta yang dapat menyelesaikan sampai akhir. 60% peserta menyatakan sangat bermanfaat, 40 persen bermanfaat. Seratus peserta menyatakan materi terkait pengelolan dan pembuatan konten materi, dan evaluasi dengan aplikasi berbasis google sangat membantu pembelajaran daring. Kendala yang dihadapi peserta adalah : waktu yang singkat, kuota internet, sinyal yg tidak selalu lancar, tidak bisa tatap muka, pembelajaran karakter tidak nampak. Kemampuan para guru menggunakan teknologi informasi dalam masa pandemik covid-19 atau kondisi normal merupakan suatu keniscayaan bagi para guru di era revolusi pendidikan 4.0.